Cytotoxicity of Zingiber officinale var. rubrum on HeLa cells and prediction of anti-proliferative activity via the jak2/stat3 and hedgehog pathways using a molecular docking approach - Siti Rofida; Laela Hayu Nurani; Dwi Utami; Citra Ariani Edityaningrum (Pharmaciana, 2023)
Cervical cancer is one of the second-leading causes of death in women. The discovery of cancer drug candidates continues to be carried out due to the resistance that occurs in cervical cancer therapy. Plant metabolite compounds are one of the sources used to explore new drug candidates. Red ginger rhizome is a candidate plant that has anti-cervical cancer activity. This study aims to determine the cytotoxicity of an ethanol extract of red ginger rhizomes on the growth of HeLa cancer cells and predict anti-proliferative activity via the jak2/stat3 and hedgehog pathways. The sample (red ginger rhizome simplicia) was extracted by remaceration using 75% ethanol. The MTT assay method is used to test the cytotoxicity and anti-proliferation of metabolite compounds using Autodock 4.2 software. The receptors used in the jak2, stat3, and smo pathways were obtained from the Protein Data Bank with the codes 6VGL, 6NUQ, and 5L7I, respectively. The ethanol extract produced is a thick yellowish brown extract with an aromatic smell and spicy taste, with an extract yield of 18.63% w/w. 75% ethanol extract of red ginger rhizomes has cytotoxic activity in HeLa cancer with an IC50 of 104.22 ± 6.18 µg/mL and an IC50 of cisplatin of 38.61 ± 3.66. Prediction of antiproliferative activity via the jak2 pathway shows a binding energy and Ki value of -7.47 kcal/mol, -7.48 kcal/mol, and 3.33 uM, 3.27 uM, as shown by alpha-cedrol and beta-eudesmol compounds. The highest inhibition on the stat3 and smo pathways was shown by the beta compound eudesmol, with binding energy and Ki values of -6.05 kcal/mol, -7.57 kcal/mol, and 36.48 uM, respectively; 2.81 uM.